2013
DOI: 10.3389/fpls.2013.00273
|View full text |Cite
|
Sign up to set email alerts
|

Plant tolerance to high temperature in a changing environment: scientific fundamentals and production of heat stress-tolerant crops

Abstract: Global warming is predicted to have a general negative effect on plant growth due to the damaging effect of high temperatures on plant development. The increasing threat of climatological extremes including very high temperatures might lead to catastrophic loss of crop productivity and result in wide spread famine. In this review, we assess the impact of global climate change on the agricultural crop production. There is a differential effect of climate change both in terms of geographic location and the crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
924
0
14

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,363 publications
(1,056 citation statements)
references
References 201 publications
25
924
0
14
Order By: Relevance
“…Drought, salt and temperatures are closely related with overlapping physiological effects (Krasensky and Jonak 2012). High temperatures, for example, frequently come with drought and water deficits, aggravating the effects of salinity and osmotic shifts on plant cells (Bita and Gerats 2013;Xiong et al 1999). Salinity is also a common feature in arid and semiarid lands where plants are convicted to tolerate osmotic stress caused by both salinity and low water potential (Rengasamy 2006).…”
Section: Map Kinase Complexity In Environmental Stresses' Signalingmentioning
confidence: 99%
“…Drought, salt and temperatures are closely related with overlapping physiological effects (Krasensky and Jonak 2012). High temperatures, for example, frequently come with drought and water deficits, aggravating the effects of salinity and osmotic shifts on plant cells (Bita and Gerats 2013;Xiong et al 1999). Salinity is also a common feature in arid and semiarid lands where plants are convicted to tolerate osmotic stress caused by both salinity and low water potential (Rengasamy 2006).…”
Section: Map Kinase Complexity In Environmental Stresses' Signalingmentioning
confidence: 99%
“…For the latter, the impact of abiotic and biotic stresses on yield should be investigated during both the vegetative and the generative phases of the plant's life cycle since both are strongly related to reproductive success. Temperature stress is one of the most detrimental abiotic stresses during the generative phase and reduced yields due to high temperatures during flowering have been reported for many species (Hedhly, 2011;Bita and Gerats, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Besides reducing water loss, this response may reflect the impact of damaged membrane integrity on the ability to maintain g s (Bita & Gerats, 2013). As discussed above, reduced g s would exacerbate the effects of heat stress on expanding leaves by further increasing their temperature and putting them at greater risk of additional heat‐induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because coffee reproduction is highly sensitive to heat (Bita & Gerats, 2013; Camargo, 1985; Camargo, 2010). Our results showed that even a short, sudden heat stress event can inhibit reproduction and have negative consequences for C. arabica productivity (Bunn et al., 2014; Davis et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation